2000
DOI: 10.1093/occmed/50.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Symptoms and Wheat Flour Exposure: A Study of Flour Millers

Abstract: The objective of this study was to determine the prevalence of respiratory symptoms and their relationship to sensitization to wheat flour allergens and fungal amylase, in a group of workers from the UK flour milling industry. A cross-sectional study was used to evaluate symptoms, using a structured interview technique, and sensitization, using skin prick test findings, from 679 employees in flour milling and packing operations at 18 flour mills. A total of 147 workers (147/679, 22%) described upper respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 10 publications
1
21
3
Order By: Relevance
“…Positive SPT to wheat grain was more prevalent among bakers compared to the control group with statistically significant difference. This is in accordance with many authors, who reported that the principal sensitizer in bread bakeries is wheat flour dust [2,3,[18][19][20][21][22]. [27] investigated pulmonary function parameters in non-smoking bakery workers and reported that the exposed group had lower forced expiratory indices than the control group.…”
Section: Disscusionsupporting
confidence: 88%
“…Positive SPT to wheat grain was more prevalent among bakers compared to the control group with statistically significant difference. This is in accordance with many authors, who reported that the principal sensitizer in bread bakeries is wheat flour dust [2,3,[18][19][20][21][22]. [27] investigated pulmonary function parameters in non-smoking bakery workers and reported that the exposed group had lower forced expiratory indices than the control group.…”
Section: Disscusionsupporting
confidence: 88%
“…This response was characterized by activation of neutrophils and fibroblasts. Similarly, Smith et al [23]described that respiratory symptoms following wheat flour exposure are due to nonspecific irritant effects. DoPico et al [24]performed inhalation provocation tests with extracts of durum wheat and durum wheat airborne dust in grain elevator workers and found 20% decrements of FEV 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, relatively large numbers of people are employed in industries processing agricultural products, and this has made the problem of exposure to vegetable dusts (grain, cotton, tobacco, tea) more serious there [WHO, 1993]. Crosssectional epidemiological studies have shown a higher prevalence of respiratory symptoms among grain handlers compared with workers not so exposed, even after controlling for the effect of smoking [Bachmann and Myers, 1991;Laraqui et al, 2000;Smith et al, 2000;Viet et al, 2001]. Among related substances, wheat dust has been most frequently implicated as an allergen for allergic rhinitis and work related asthma in cereal flour workers [Prichard et al, 1994].…”
Section: Introductionmentioning
confidence: 99%